Ambler family papers
Land records including bonds, deeds, grants, indentures, surveys, and other papers from the vicinity of James City County, Va., and the Fairfax proprietary estates of the Northern Neck of Virginia. Names represented include Richard Ambler and family, Robert Anderson, Sir Edmund Andros, Nathaniel Bacon, Sir William Berkeley, Beverley family, Robert Carter, Col. Edward Chilton, Lady Marguritte Culpeper (Culpepper) and family, Lord Howard of Effingham, Lord Thomas Fairfax, Sir William Gooch, Henry Hartwell, Thomas Hollyday, Francis Nicholson, Isham Randolph and family, and Alexander Spotswood.
In part, transcribed by Lindsay O. Duvall in "James City County, Virginia, 1634-1904," Virginia Colonial Abstracts, series 2, volume 4 (1978).
Collection material in English.
Keywords: Ambler, Richard, -- 1690-1766.; Anderson, Robert, -- 1712-1792; Andros, Edmund, -- Sir, -- 1637-1714.; Bacon, Nathaniel, -- 1648-1676.; Berkeley, William, -- Sir, -- 1605-1677.; Carter, Robert, -- 1663-1732.; Chilton, Edward; Culpeper, Marguritte, -- Lady; Effingham, Kenneth Alexander Howard, -- Earl, -- 1767-1845.; Fairfax, Thomas Fairfax, -- Lord, -- 1692-1782.; Gooch, William, -- Sir, -- 1681-1751.; Hartwell, Henry; Hollyday, Thomas; Nicholson, Francis, -- 1655-1728.; Randolph, Isham, -- 1685-1742.; Spotswood, Alexander, -- 1676-1740.; Ambler family; Beverly family; Culpepper family; Randolph family; Bonds -- Virginia -- James City County; Bonds -- Virginia -- Northern Neck; Deeds -- Virginia -- James City County; Deeds -- Virginia -- Northern Neck; Land grants -- Virginia -- James City County; Land grants -- Virginia -- Northern Neck; Land tenure -- Virginia -- James City County; Land tenure -- Virginia -- Northern Neck; James City County (Va.) -- Surveys; Northern Neck (Va.) -- Surveys; Virginia -- History